Accident investigation ([S.l.] : Safetycare Australia, 1991)
This video will show how to identify the real causes of an accident and how to determine corrective actions that, when implemented, will prevent a recurrence of the same type of accident
Accompanied by 1 set of training course for users
Keywords: Accidents -- Prevention